TINJAUAN YURIDIS MENGENAI IMPEMENTASI PUTUSAN MAHKAMAH ARBITRASE INTERNASIONAL DITINJAU DARI PUTUSAN “PERMANENT COURT OF ARBITRATION CASE NO. 2013-19” ANTARA FILIPINA DAN CHINA TENTANG CLAIM ATAS PERAIRAN NATUNA DI LAUT CHINA SELATAN - Nico Hermawan Sipayung; Suhaidi Suhaidi; Makdin Munthe (Journal of USU International Law, 2020)
ABSTRACT Nowadays, arbitration institutions are increasingly recognized by the public as an alternative to dispute resolution other than through the courts both in Indonesia and internationally. However, this does not mean that the method of resolving disputes through arbitration is the perfect method. Arbitration has several weaknesses, especially in terms of the recognition and implementation of international arbitration decisions. Arbitration does not have the power or authority to execute its decisions. In practice, a court has the authority to reject an international arbitration award. In this regard, this study aims to find out how the implementation of the International Arbitration Court's decision in adjudicating a regional dispute between countries. In addition, this study will also analyze decisions aimed at resolving disputes over a region's claims. This research uses a normative juridical approach. The writing method used in this study is library research through an inventory of materials from books, journals, articles, dictionaries, international legal instruments and other scientific writing related to this research. Based on the research that has been done, it can be concluded that the International Arbitration Court has the authority to decide on a territorial dispute in which the two disputing countries have been bound by a convention and deemed to have complied and obeyed the agreement made. It should be noted that in this regard, China as the defendant has ratified UNCLOS 1982 and is also a member of the United Nations. This became a bright spot in the dispute over the South China Sea waters involving the Philippines as the plaintiff. The issue of the fall of the International Arbitration Court's decision arises because of the response from China to boycott the judicial body.